2015
DOI: 10.2147/ijn.s74079
|View full text |Cite
|
Sign up to set email alerts
|

Lower irritation microemulsion-based rotigotine gel: formulation optimization and in vitro and in vivo studies

Abstract: Background Rotigotine is a potent and selective D 1 , D 2 , and D 3 dopaminergic receptor agonist. Due to an extensive first-pass effect, it has a very low oral bioavailability (approximately 0.5% in rats). Purpose The present investigation aimed to develop a microemulsion-based hydrogel for transdermal rotigotine delivery with lower application site reactions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The in vitro permeation of optimized KME depicted that ketoconazole from KME permeated through the membrane by approximately 30 %, whereas it was retained in the membrane by approximately 60 % after 24 h. Our result was in accordance with a previous study that reported the combination of microemulsions with reduced water content revealed high drug deposition in the skin [35]. It is hypothesized that increasing Smix would reduce the skin hydration and permeation flux, and the small particle size of microemulsions would provide a large surface area for drug penetration [44,45]. Regarding the high skin retention, it is indicated that KME could effectively retain in the skin layer within the area of the target infection site and could have a longer antifungal action.…”
Section: Antifungal Activitysupporting
confidence: 92%
“…The in vitro permeation of optimized KME depicted that ketoconazole from KME permeated through the membrane by approximately 30 %, whereas it was retained in the membrane by approximately 60 % after 24 h. Our result was in accordance with a previous study that reported the combination of microemulsions with reduced water content revealed high drug deposition in the skin [35]. It is hypothesized that increasing Smix would reduce the skin hydration and permeation flux, and the small particle size of microemulsions would provide a large surface area for drug penetration [44,45]. Regarding the high skin retention, it is indicated that KME could effectively retain in the skin layer within the area of the target infection site and could have a longer antifungal action.…”
Section: Antifungal Activitysupporting
confidence: 92%
“…There is currently a lower irritation microemulsion-based RTG gel being studied and in the future, there may be formulations of RTG with less application site reactions. 58 Future comparator studies could better characterize the benefits of the RTG against other generic alternatives, and to better inform the clinician when choosing a therapy for PD or RLS.…”
Section: Discussionmentioning
confidence: 99%
“…MEs may act as drug reservoirs, with the drug being released from the inner phase to the outer phase and then onto the skin. Furthermore, the MEs may affect the stratum corneum structure and reduce the diffusional barrier by acting as a permeation enhancer (26,33). …”
Section: Resultsmentioning
confidence: 99%